Perlindungan Hukum Korban Tindak Pidana Marital Rape terhadap Perempuan dalam Perkawinan Dibawah Tangan - Sinaga, Dahato Fontana Sinaga; Maria Novita Apriyani (LPPM Universitas Ekasakti Padang, 2024)
Rape does not only occur in the realm outside of marriage, it is even now recognized as rape within marriage (marital rape) which is vulnerable to occurring in underhanded marriages. The aim of this research is to explore forms of legal protection for women as victims of criminal acts marital rape in underhanded marriages according to the Criminal Code and Law Number 1 of 2023 as well as according to Law Number 23 of 2004 and Law Number 12 of 2022. This research method uses a normative juridical research type with a statutory and legal conceptual approach. The research results found that there is a form of legal protection for women as victims of criminal acts marital rape in underhanded marriage according to the old Criminal Code it had not been realized at all, whereas in Law Number 1 of 2023 it had been realized in a preventive as well as repressive form. Meanwhile, according to Law Number 23 of 2004 and Law Number 12 of 2022, legal protection has also been provided, but it is not specifically related to criminal acts. marital rape This occurs in a marital relationship under the hand. Thus, the form of legal protection cannot be realized specifically for victims.